CONTAMINACIÓN DE LOS PARQUES PÚBLICOS DE LOS DISTRITOS DE LIMA OESTE CON HUEVOS DE Toxocara sp. - López T., Francisco (2005)
The objective of this study was to determine the level of contamination of public parks with Toxocara sp. eggs in Western Lima. Soil and grass samples were collected using the Double W method from April till August 1999 in 123 public parks of the districts of Breña, Jesus María, La Victoria, Lima, Lince, Magdalena del Mar, Miraflores, Pueblo Libre, San Borja, San Isidro, San Luis, San Miguel and Surquillo. The temperature varied between 24.4 and 16.2 ºC and the mean monthly relative humidity was 91.5%. The results showed that 78 parks were positive to Toxocara sp. eggs, which represents a prevalence of 63 ± 9%. Parks were classified according to the degree of conservation and to the socioeconomic status of the inhabitants. The well, average, and poorly maintained parks had 71, 50, and 50% of contamination, respectively. Parks located in areas of high socioeconomic status were more contaminated than those located in areas of low socioeconomic status (69.2, 66.6, 50.0, 50.0, and 33.3% in high, medium high, medium, medium low, and low, respectively). Toxocara sp. eggs found in these parks were viable as indicated through lesions develoved by experimentally infected quails. It is necessary to regulate the entrance of dogs in public parks and to inforce the implementation of latrines for pets.